أثر ألفية ابن مالك في التفكير النحوي العربي - جاموس، عبد الله محمود (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
"Al-Khulasah Al-Alfiyyah", written by Jamal Al-Din Muhammad bin Abdullah bin Malik Al-Taei Al-Jayani, who died in 672 AH in Damascus is one of the most famous analysis of grammatical systems and the most widely distributed publication among scholars, grammarians and students. This is because Ibn Malik has a distinguished position among the scholars and they respect him highly due to of the depth of his knowledge. He was an imam in many of the arts; the seven modes of recitations, Hadith, language, grammar, declension, poetries of the Arabs, jurisprudence and so on, in addition to religion, ethics, perfection of the mind, sincerity and reverence. The fame of Alfiyyah comes as it contains simple words, exquisite structure, precise limits and definitions. They are removed from tradition, scientific terminology, familiarity of grammatical sections. It is an exquisite coordination of the order of those sections and the rules are based on solid bases. Also, the effects of Al-Alfiyyah is clear as an unequalled phenomenon in grammatical lessons, in the works and authors of grammars and in the opinions of the grammarians who studied and accepted it. Due to the interested of scholars in Alfiyyah, many senior grammarians have explained it, including: Al-Badr Ibn Al-Nazim, Ibn Hisham, Ibn Aqil, Abu Haian, Al-Muradi, Ibn Al-Wardi, Al-Shatibi, Al-Makodi, Al-Ashmouni, Ibrahim bin Qayem Al-Jawziyah, Ibn Ghazi Al-Muknasi and many others. The explanations and the footnotes of Alfiyyah reached nearly one hunderd. The lasting effects of this work by Ibn Malik and what he did in Alfiyyah can be clearly seen in those explanations and footnotes of the works of grammar and his writings, in books of interpretations and others. Because of all the points mentioned above, this study traces those effects left by Alfiyyah on the scholars, grammarians and students, in grammatical work and literature that were written after Alfiyyah. They were influenced by it and in grammar lessons in general until now. Moreover, what Alfiyyah illustrates reflect a historical turning point in the path of grammar and its compositions in terms of grammatical rules and terms, order of sections, choices and singularities, etc. This results in a huge scientific movement represented in the many works that were associated with Alfiyyah and scientific studies.